Seasonal Variations in Hydrographical Parameters, Nutrient Content and Energy Content of the Suspended Particulate Matter in Netravathi - Gurpur Estuary - A.P., Vedamurthy; T.J., Ramesha; M.T., Lakshmipathi; V., Hariharan (Fishery Technology, 2025)
An attempt has been made to study the energy content distribution in the suspended particulate matter of Netravathi-Gurpur estuary. Hydrological parameters and nutrient content exhibited seasonal variations. Suspended particulate matter gradually increased from January onwards till May at all the stations. The higher particulate matter concentration of 218 mg. I"1 was reported in the month of December. The energy content of detrital matter was less during June to September in spite of greater concentration.